Listening Advanced / Oxford Supplementary Skills - Breary Barry; Maley Alan; Revell Jane (Oxford University Press, 1988)
This material provide students with interesting and informative texts as well as challenging tasks to help them develop their listening skills. Foreword, Introduction, Frightfully Super, Does It Have to Be Grim?, For Everything, Genre, Bulletins, Medicine Matters, Diamond Demand, Flying Around Freely, Egypt for the Day, Throwing the Voice...Catching the Drift, Key, Text of Recordings.